Methanogen community dynamics within a dry anaerobic digester - Bartell, Ryan D. (My University, 2015)
Greenhouse gasses such as methane and carbon dioxide are thought to play a major role in global climate change. Anthropogenic methane is derived mainly from energy production, agricultural sources, and waste management practices. Anaerobic digesters function to produce energy using the methane derived from organic matter which would typically be deposited in landfills. The three main types of digesters are low solids wet digesters, high solids wet digesters, and dry anaerobic digesters. The dry anaerobic digester, which is the least common type, has relatively high solids content with very few moving parts, and the bulk phase of the system is solid instead of liquid. Due to the rarity of dry anaerobic digesters, the microbial community responsible for the production of biogas is less-studied than in other types of digesters. Biogas, which is usually comprised of methane, carbon dioxide, and hydrogen sulfide, is produced as a result of four metabolic steps which include hydrolysis, acidogenesis, acetogenesis, and methanogenesis. In hydrolysis, acidogenesis, and acetogenesis, bacteria break down organic matter, and in methanogenesis archaea use the products of acidogenesis and acetogenesis to produce methane. The main objective of this research was to determine if a fluctuation pattern in the concentrations of two orders methanogenic archaea (Methanosarcinales and Methanomicrobiales) existed over a 28-day fermentation in a dry anaerobic digester. To address this objective, taxonomic groups present within the digester were determined by 454-pyrosequencing, and the biogas composition and volume were characterized. The 16S rRNA gene copy concentrations of Methanosarcinales spp. and Methanomicrobiales spp. were determined using qPCR. Bench-scale biogas experiments were conducted with and without substrate, and biological samples were collected at regular time intervals for qPCR analysis. Pyrosequencing results indicate that within the dominate class Methanomicrobia, the orders Methanosarcinales (73.7%) and Methanomicrobiales (26.2%) were most common in the tested anaerobic digester before biogas experiments. Biogas experiments show that fermenters with substrate produce a greater volume of biogas and methane than those without substrate. qPCR analysis showed that during the 28-day fermentation, Methanosarcinales spp. were present at approximately 107 16S genes per gram of sample, whereas Methanomicrobiales spp. had concentrations between 104 and 106 16S genes per gram of sample. Overall, Methanosarcinales was consistently more abundant at every tested time point. The different concentrations of methanogens could indicate that the nutrients and conditions within the tested digester are more suited to the metabolism of Methanosarcinales spp. than Methanomicrobiales spp. This information could be used in the future to dictate the type of substrate used in a particular dry anaerobic digester.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Mater of Science-Biology Microbiology
Keywords: Sewage - purification - anaerobic tretment; Compost plants - Technological innovations; Refuse and refuse disposal - biodegradation; Renewable energy